2019
DOI: 10.4067/s0718-19572017000100012
|View full text |Cite
|
Sign up to set email alerts
|

Identificación de zonas propicias para el desarrollo larval de la macarela del Pacífico (Scomber japonicus) en la porción sur de la Corriente de California

Abstract: Abstract.-Larval size is considered as an important variable to understand the changes in larval development and identification of a suitable environment for larval growth and survivor. Larvae of the Pacific mackerel (Scomber japonicus) have a slow growth during the early stages of development (6-8 mm SL); subsequently, the growth rate increases, but the development depends mainly on the temperature and food. The aim of this study was to identify the areas and seasons favorable for larval development of S. jap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 15 publications
3
4
0
Order By: Relevance
“…OA estimated for the analyzed larvae showed that only 10.30% of the observed morphological changes corresponded to changes associated with growth (allometry). These results are consistent with the isometric analysis performed by Anaya‐Godínez et al (2017) and similar to those observed in larvae of mesopelagic fish, such as myctophids Diogenichthys atlanticus (9.75%) and Diogenichthys laternatus (9.73%; Zavala‐Muñoz et al, 2019). In contrast, some cryptobenthic species change with habitat through their ontogeny (neritic to benthic) with higher OA: Myxodes viridis (Clinidae) 14.69% (Zavala‐Muñoz et al, 2016), Auchenionchus crinitus (Labrisomidae) between 19.30% and 29.92% (Landaeta et al, 2019), and Sicyases sanguineus (Gobiesocidae) 31.69% (Bernal‐Durán & Landaeta, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…OA estimated for the analyzed larvae showed that only 10.30% of the observed morphological changes corresponded to changes associated with growth (allometry). These results are consistent with the isometric analysis performed by Anaya‐Godínez et al (2017) and similar to those observed in larvae of mesopelagic fish, such as myctophids Diogenichthys atlanticus (9.75%) and Diogenichthys laternatus (9.73%; Zavala‐Muñoz et al, 2019). In contrast, some cryptobenthic species change with habitat through their ontogeny (neritic to benthic) with higher OA: Myxodes viridis (Clinidae) 14.69% (Zavala‐Muñoz et al, 2016), Auchenionchus crinitus (Labrisomidae) between 19.30% and 29.92% (Landaeta et al, 2019), and Sicyases sanguineus (Gobiesocidae) 31.69% (Bernal‐Durán & Landaeta, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, Magdalena Bay is considered an overlap zone for both groups (Gluyas‐Millán & Quiñónez‐Velázquez, 1996). Larval morphological differences are consistent with the other evidence of these stocks (Anaya‐Godínez et al, 2017).…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations